Psy wojny kontra kundle pokoju: siła hybrydowości w powieści Vieta Thanha Nguyena „Sympatyk" - Aleksandra Hołubowicz (Jednak Książki, 2023)
The protagonist-narrator of Viet Thanh Nguyen’s novel, as he often repeats, is a person of two minds. As the child of a Vietnamese woman and a French Catholic priest, he becomes a „hybrid” on the genetic level and later also in the cultural sphere. His upbringing has not only been influenced by the Catholic religion, communist indoctrination but also by the American literary canon, as he has graduated from a literary studies program in the US. He is a communist spy in the South Vietnamese Army during the war, and after the fall of South Vietnam he escapes to the United States as one of the few refugees. Loyal to the communist revolution in the US, he continues his intelligence activities going to any lengths and using any means considered necessary. The nameless narrator is not only a character that reminds a hero from a Hollywood action movie, but also a hybrid – a man who, through diversity or perhaps the merging of mutually exclusive identities, inhabits the sphere in between. This phenomenon, called nepantlerismo by Gloria Anzaldúa, means consciously navigating the gaps between the binary oppositions of those who belong to neither of the two sides. In the article, I look at the phenomenon of hybridity and consider to what measure it can be seen as an antidote to national chauvinism, imperialism and violence. I also examine what Viet Thanh Nguyen in his scholarly work calls the „industrialization of memory,” viewing Hollywood as a tool for producing memories of the Vietnam War operating within the US military-industrial complex.